Method for synchronously preparing carbon quantum dots and lignin from papermaking black liquor

By diluting and acidizing the papermaking black liquid, separating and purifying the carbon quantum dots and lignin on stand, the problem of synchronous preparation is solved, and carbon quantum dots and lignin is prepared at low cost and efficiently, and is used to photocatalytic degradation of pollutants.

CN120463185APending Publication Date: 2025-08-12NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510345122.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently use papermaking black liquid to synchronize carbon quantum dots and lignin, resulting in resource waste and environmental pollution problems.

Method used

The reaction was carried out by diluting the papermaking black liquid and adding a strong acid solution. After standing precipitation, the supernatant and precipitate were separated. The carbon quantum dots and lignin were obtained respectively. The carbon quantum dots were purified by dialysis and freeze-drying technology, and the catalyst was prepared in combination with TiO2 for photocatalytic degradation of pollutants.

Benefits of technology

Low-cost and simple carbon quantum dots and lignin preparation are achieved, the yield of carbon quantum dots is improved, and high-efficiency catalytic performance is shown in photocatalytic degradation of pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463185A_ABST
    Figure CN120463185A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synchronously preparing carbon quantum dots and lignin from papermaking black liquor, which comprises the following steps: by taking waste black liquor generated in a papermaking pulping process as a raw material, adding sulfuric acid under a mild condition to separate out lignin, and dialyzing and drying supernate to obtain the carbon quantum dots. The carbon quantum dots prepared by the method have good physicochemical properties and have great application potential in the fields of photocatalysis and the like; the method for synchronously preparing the carbon quantum dots and the lignin from the papermaking black liquor is green and environment-friendly, mild in preparation condition, simple and convenient in process, low in cost and high in carbon quantum dot yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomass carbon quantum dot preparation, and specifically relates to a method for synchronously preparing carbon quantum dots and lignin from papermaking black liquor. Background Art

[0002] With the sustained growth of my country's economy, the papermaking industry has experienced large-scale development. Papermaking black liquor, wastewater generated by the alkaline pulping process, is the primary source of pollution in paper mills, accounting for over 90% of total pollution emissions. Black liquor contains large amounts of organic matter (especially lignin) and inorganic salts. Through proper treatment, it can be converted into a variety of resources, achieving a unified economic, environmental, and social benefit.

[0003] Lignin, a polymer composed of phenylpropane structural units linked by carbon-carbon and ether bonds, is an excellent raw material for the development of a variety of high-value-added products. Acidification of papermaking black liquor with inorganic acids to precipitate lignin is a common method for obtaining lignin. This method of lignin recovery from papermaking black liquor is simple, low-cost, and offers high extraction yields, making it particularly suitable for large-scale industrial production.

[0004] Carbon quantum dots (CQDs) are a new class of high-value carbon nanomaterials with sizes less than 10 nm. Compared to traditional metal quantum dot materials, CQDs possess excellent hydrophilicity, low toxicity, and controllable fluorescence, enabling applications in metal ion detection, bioimaging, sensing, solar cells, and photocatalysis. Currently, CQDs are primarily prepared using precursors such as graphene, activated carbon, and polyvinyl alcohol, which presents challenges such as high cost, complex processes, and the inability to mass-produce them. Lignocellulosic biomass, rich in carbon and active functional groups, is an ideal raw material for preparing CQDs. Typically, CQDs are formed by subjecting biomass to a long-term hydrothermal reaction (several to over ten hours) at high temperatures (180-200°C). In the alkaline pulping process, biomass feedstock is steamed with a sodium hydroxide (and sodium sulfide) solution at high temperatures (150-170°C) and high pressure for several hours. Under these conditions, quantum dots form and are present in black liquor alongside sodium lignin salts.

[0005] In the past, the acid precipitation process for papermaking black liquor was only focused on recovering lignin precipitates, while the supernatant was treated as waste liquid. Therefore, it is of great significance to achieve the simultaneous preparation of carbon quantum dots and lignin from black liquor. Summary of the Invention

[0006] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of this application to avoid obscuring the purpose of this section, the abstract and the title of the invention, and such simplifications or omissions should not be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for simultaneously preparing carbon quantum dots and lignin from papermaking black liquor.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for synchronously preparing carbon quantum dots and lignin from papermaking black liquor, comprising:

[0010] The papermaking black liquor is diluted with deionized water to obtain a diluted black liquor solution;

[0011] The strong acid solution is added to the heated diluted black liquor solution and stirred continuously to allow it to react fully;

[0012] The solution after the reaction is allowed to settle to obtain a supernatant and a precipitate;

[0013] Add deionized water to the primary precipitate, stir thoroughly, and let it stand again to obtain a secondary supernatant and a secondary precipitate;

[0014] The primary precipitate and the secondary precipitate are combined and fully dried in an oven at 60°C to obtain lignin;

[0015] The primary supernatant and the secondary supernatant are combined, centrifuged, filtered through a microporous membrane, and the pH value of the solution is adjusted to 6-7. The obtained solution is placed in a dialysis bag for dialysis. The dialyzed carbon quantum dot solution is placed in a freeze dryer and freeze-dried to obtain carbon quantum dot powder.

[0016] The concentration of the strong acid solution is 40-80%, and the temperature of the heated black liquor solution is 40-80°C.

[0017] As a preferred embodiment of the method of the present invention, the ratio of the diluted black liquor solution to the strong acid solution is 10 to 20:1.

[0018] As a preferred embodiment of the method of the present invention, the ultrasonic oscillation time is 20 to 40 minutes.

[0019] As a preferred embodiment of the method of the present invention, the strong acid solution is a sulfuric acid solution, a hydrochloric acid solution and a phosphoric acid solution.

[0020] As a preferred embodiment of the method of the present invention, the concentration of the strong acid solution is 60-80%.

[0021] As a preferred embodiment of the method of the present invention, the static sedimentation time is 12 to 20 hours.

[0022] As a preferred embodiment of the method of the present invention, the pore size of the microporous filter membrane is 0.22 to 0.35 μm.

[0023] Another object of the present invention is to provide the use of carbon quantum dots as catalysts in photocatalytic degradation of pollutants.

[0024] As a preferred solution of the application of the present invention, the application method includes:

[0025] The carbon quantum dots and TiO2 were mixed and placed in a reactor, ultrasonically shaken, and reacted in a muffle furnace. After the reaction was completed, the mixture was cooled to room temperature to obtain a solid-liquid mixture.

[0026] After the solid-liquid mixture is washed and centrifuged, the precipitate is dried and ground to obtain carbon quantum dots / TiO2 catalyst powder.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention uses papermaking black liquor as raw material, has low cost, and can realize the recycling of waste pollutants.

[0029] (2) The preparation conditions of the present invention are mild and the process is simple.

[0030] (3) The present invention can obtain two high-value products: carbon quantum dots and lignin.

[0031] (4) Compared with most technologies for preparing carbon quantum dots from lignocellulosic biomass, the method of the present invention has a high yield of carbon quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort. Among them:

[0033] Figure 1 This is a TEM image of the carbon quantum dots prepared in Example 1 of the present invention.

[0034] Figure 2 This is the HR-TEM image of the carbon quantum dots prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.

[0038] The raw materials and reagents used in the present invention are as follows: papermaking black liquor containing 63.75% solids of poplar and reed was provided by a paper mill in Hunan; straw black liquor (containing 36.25% solids) and poplar and eucalyptus black liquor (containing 48.76% solids) were provided by a paper mill in Shandong; concentrated sulfuric acid (AR), concentrated hydrochloric acid (AR), concentrated phosphoric acid (AR), sodium hydroxide (AR), and methylene blue (AR) were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.; nano-titanium dioxide (99%, <100 nm) and dialysis bag (500 Da) were purchased from Aladdin; and microporous filter membrane (0.22 μm) was purchased from Tianjin Jinteng Laboratory Equipment Co., Ltd.

[0039] Example 1

[0040] This embodiment provides a method for simultaneously preparing carbon quantum dots and lignin from papermaking black liquor

[0041] (1) Weigh 1 g of papermaking black liquor and place it in a beaker. Add 40 mL of deionized water to the beaker and place it in an ultrasonic shaker for 20 minutes.

[0042] (2) After the black liquor is fully dissolved, place the beaker containing the black liquor in a constant temperature water bath and heat it to 60°C. Add 2 mL of 60% sulfuric acid solution into the black liquor solution and stir continuously to allow it to react fully.

[0043] (4) The solution after the reaction was allowed to stand for 12 hours and the supernatant was collected; 20 mL of deionized water was added to the remaining precipitate, stirred thoroughly, and allowed to stand for another 12 hours, and the supernatant was collected.

[0044] (5) The two precipitates are fully dried in an oven at 60°C to obtain lignin.

[0045] (6) The supernatants obtained from the two times were combined, centrifuged at 7000 rpm for 6 min, filtered through a 0.22 μm microporous filter membrane, and the pH value of the solution was adjusted to 7 with NaOH solution to obtain a crude carbon quantum dot product solution.

[0046] (7) The crude carbon quantum dot solution was placed in a 500Da dialysis bag and dialyzed in 4000mL of deionized water for 72h, during which the deionized water was replaced every 6h. The dialyzed carbon quantum dot solution was placed in a freeze dryer and freeze-dried for 24h to obtain the carbon quantum dot powder of Example 1. The TEM image of the carbon quantum dots is shown in FIG. Figure 1 As shown, the HR-TEM images of carbon quantum dots are as follows Figure 2 shown Figure 1 It is clearly shown that the particle size of CQDs is significantly smaller than 10 nm, they are evenly dispersed in aqueous solution, and are zero-dimensional spherical particles. Figure 2 Obvious lattice fringes can be seen, and the lattice fringes spacing inside the CQDs core is measured to be 0.21 nm, corresponding to the (100) crystal plane of graphitic carbon.

[0047] The mass yield of carbon quantum dots and lignin is the mass percentage of the obtained product to the absolute dry black liquor. The specific calculation formula is:

[0048] θ=m / ηm0×100%

[0049] θ——mass yield, in %;

[0050] η——solid content of black liquor, here η=63.75%;

[0051] m, m0 - the mass of the product and the mass of the black liquor raw material, in g.

[0052] The mass yield of the carbon quantum dots prepared in Example 1 was 12.39%, the relative quantum yield was 8.09%, the mass yield of lignin was 27.54%, and the total mass yield of the carbon quantum dots and lignin was 39.93%.

[0053] Example 2

[0054] The difference between this embodiment and embodiment 1 is that the 60% sulfuric acid solution in step 2 is replaced by an 80% sulfuric acid solution.

[0055] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0056] The mass yield of the carbon quantum dots prepared in this example was 12.30%, the relative quantum yield was 7.90%, the mass yield of lignin was 30.26%, and the total mass yield of the carbon quantum dots and lignin was 42.56%.

[0057] Example 3

[0058] The difference between Example 1 and Example 1 is that heating to 60°C in step 2 is replaced by heating to 80°C.

[0059] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0060] The mass yield of the carbon quantum dots prepared in this example was 12.15%, the relative quantum yield was 8.05%, the mass yield of lignin was 22.66%, and the total mass yield of the carbon quantum dots and lignin was 34.82%.

[0061] Example 4

[0062] The difference between this embodiment and embodiment 1 is that the 60% sulfuric acid solution in step 2 is replaced by a 40% sulfuric acid solution.

[0063] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0064] The mass yield of the carbon quantum dots prepared in this example was 10.21%, the relative quantum yield was 7.13%, the mass yield of lignin was 28.07%, and the total mass yield of the carbon quantum dots and lignin was 38.28%.

[0065] Example 5

[0066] The difference between Example 1 and Example 1 is that heating to 60°C in step 2 is replaced by heating to 40°C.

[0067] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0068] The mass yield of the carbon quantum dots prepared in this example was 11.81%, the relative quantum yield was 6.79%, the mass yield of lignin was 29.66%, and the total mass yield of the carbon quantum dots and lignin was 41.47%.

[0069] Example 6

[0070] The difference between Example 1 and Example 1 is that in step 1, papermaking black liquor is replaced by straw black liquor.

[0071] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0072] The mass yield of the carbon quantum dots prepared in this example was 20.43%, the relative quantum yield was 9.61%, the mass yield of lignin was 0.61%, and the total mass yield of the carbon quantum dots and lignin was 21.04%.

[0073] Example 7

[0074] The difference between Example 1 and Example 1 is that the papermaking black liquor in step 1 is replaced by poplar and arborvitae black liquor.

[0075] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0076] The mass yield of the carbon quantum dots prepared in this example was 12.14%, the relative quantum yield was 15.04%, the mass yield of lignin was 7.38%, and the total mass yield of the carbon quantum dots and lignin was 19.52%.

[0077] As can be seen from Example 1 and Comparative Examples 9-10, the mass yields of carbon quantum dots and lignin prepared from different types of black liquor vary significantly. The highest mass yield of lignin was obtained from black liquors made from poplar and reed wood; the highest mass yield of carbon quantum dots was obtained from black liquor made from straw; and the highest relative quantum yield of carbon quantum dots was obtained from black liquors made from poplar and eucalyptus wood, demonstrating the superior fluorescence properties of the method. This demonstrates the universal applicability of the present invention to black liquor.

[0078] Example 8

[0079] This embodiment provides the application of carbon quantum dots

[0080] 1. Preparation of carbon quantum dots / TiO2 catalyst powder

[0081] Take 0.005 g of the carbon quantum dots prepared in Example 1 and 0.5 g of TiO2 doped into a 50 mL reactor, ultrasonically vibrate for 20 min, place it in a muffle furnace at 180 ° C to react for 4 h, cool to room temperature, centrifuge the obtained solid-liquid mixture at 7000 r / min for 6 min, wash the precipitate with deionized water and centrifuge it twice again, take the precipitate, dry it, and grind it to obtain carbon quantum dot / TiO2 catalyst powder.

[0082] 2. Application of carbon quantum dot-modified TiO2 catalysts in photocatalytic degradation of pollutants

[0083] Control group: 100 mL of 10 mg / L methylene blue (MB) solution without adding catalyst.

[0084] Experimental Group 1: 50 mg of the powdered carbon quantum dots / TiO2 catalyst prepared in Example 2 was dispersed in 100 mL of 10 mg / L methylene blue (MB) solution.

[0085] Experimental group 2: 50 mg of powdered TiO2 was dispersed in 100 mL of 10 mg / L methylene blue (MB) solution.

[0086] Each solution was stirred magnetically in the dark for 30 min and then irradiated with a 300W xenon lamp (100 mW·cm -2 ) for photocatalytic degradation.

[0087] During the photocatalytic degradation of pollutants, 2 to 3 mL of the suspension was taken out every 20 min using a microsyringe, and the concentration of the supernatant was measured using an ultraviolet-visible spectrophotometer at 664 nm.

[0088] The control group and experimental groups 1 and 2 were used in the photocatalytic degradation experiment. After 2 hours of photocatalytic degradation, the degradation efficiency of the control group 1 was 32.5%, the degradation efficiency of the experimental group 1 was 69.6%, and the degradation efficiency of the experimental group 2 was 51.7%.

[0089] In summary, the photocatalytic degradation of MB was performed using no catalyst, TiO2 alone, and carbon quantum dots / TiO2. The degradation efficiency was significantly higher with the addition of a catalyst than without. The photocatalytic degradation efficiency of the carbon quantum dots / TiO2 reached 69.6%, exceeding the 51% efficiency when using TiO2 alone. This indicates that doping carbon quantum dots with the semiconductor TiO2 can improve the efficiency of photocatalytic degradation of pollutants, providing research direction for the application of carbon quantum dots in photocatalysis.

[0090] Comparative Example 1

[0091] The difference between this embodiment and embodiment 1 is that the 60% sulfuric acid solution in step 2 is replaced by a 20% sulfuric acid solution.

[0092] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0093] The mass yield of the carbon quantum dots prepared in this example was 8.69%, the relative quantum yield was 6.08%, the mass yield of lignin was 27.04%, and the total mass yield of the carbon quantum dots and lignin was 35.74%.

[0094] Comparative Example 2

[0095] The difference between this embodiment and embodiment 1 is that the 60% sulfuric acid solution in step 2 is replaced by a 100% sulfuric acid solution.

[0096] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0097] The mass yield of the carbon quantum dots prepared in this example was 5.07%, the relative quantum yield was 8.99%, the mass yield of lignin was 29.55%, and the total mass yield of the carbon quantum dots and lignin was 34.62%.

[0098] Comparative Example 3

[0099] The difference between this embodiment and comparative example 2 is that heating to 60° C. in step 2 is replaced by heating to 20° C.

[0100] The remaining steps and processes are all referred to Comparative Example 4 to obtain the carbon quantum dots of this embodiment.

[0101] The mass yield of the carbon quantum dots prepared in this example was 4.44%, the relative quantum yield was 6.59%, the mass yield of lignin was 33.78%, and the total mass yield of the carbon quantum dots and lignin was 38.22%.

[0102] Comparative Example 4

[0103] The difference between this embodiment and comparative example 2 is that heating to 60° C. in step 2 is replaced by heating to 40° C.

[0104] The remaining steps and processes are all referred to Comparative Example 4 to obtain the carbon quantum dots of this embodiment.

[0105] The mass yield of the carbon quantum dots prepared in this example was 4.03%, the relative quantum yield was 8.63%, the mass yield of lignin was 33.90%, and the total mass yield of the carbon quantum dots and lignin was 37.93%.

[0106] Comparative Example 5

[0107] The difference between this embodiment and comparative example 2 is that heating to 60° C. in step 2 is replaced by heating to 80° C.

[0108] The remaining steps and processes are all referred to Comparative Example 4 to obtain the carbon quantum dots of this embodiment.

[0109] The mass yield of the carbon quantum dots prepared in this example was 4.99%, the relative quantum yield was 5.50%, the mass yield of lignin was 20.20%, and the total mass yield of the carbon quantum dots and lignin was 25.18%.

[0110] Comparative Example 6

[0111] The difference between Example 1 and Example 1 is that heating to 60°C in step 2 is replaced by heating to 20°C.

[0112] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0113] The mass yield of the carbon quantum dots prepared in this example was 6.94%, the relative quantum yield was 6.85%, the mass yield of lignin was 32.48%, and the total mass yield of the carbon quantum dots and lignin was 39.42%.

[0114] Comparative Example 7

[0115] The difference between this embodiment and embodiment 1 is that the 60% sulfuric acid solution in step 2 is replaced by a 60% hydrochloric acid solution.

[0116] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0117] The mass yield of the carbon quantum dots prepared in this example was 12.39%, the relative quantum yield was 5.28%, the mass yield of lignin was 30.45%, and the total mass yield of the carbon quantum dots and lignin was 42.82%.

[0118] Comparative Example 8

[0119] The difference between Example 1 and Example 1 is that the 60% sulfuric acid solution in step 2 is replaced by a 60% phosphoric acid solution.

[0120] The remaining steps and processes are all referred to Example 1 to obtain the carbon quantum dots of this embodiment.

[0121] The mass yield of the carbon quantum dots prepared in this example was 8.75%, the relative quantum yield was 7.38%, the mass yield of lignin was 30.14%, and the total mass yield of the carbon quantum dots and lignin was 38.89%.

[0122] Carbon quantum dots were prepared under different reaction temperatures, different acid concentrations and different acid types. The results showed that when the reaction temperature was 60°C and the added acid was 60% sulfuric acid, the mass yield of carbon quantum dots was the highest. Therefore, this working condition is the optimal working condition for the mass yield of carbon quantum dots. Temperature has a greater influence on the mass yield of lignin. As the temperature increases, the yield of lignin gradually decreases. When the reaction temperature is 20°C and the added acid is 60% sulfuric acid, the mass yield of lignin is the highest.

[0123] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for synchronously preparing carbon quantum dots and lignin from papermaking black liquor, characterized in that: include, The papermaking black liquor is diluted with deionized water to obtain a diluted black liquor solution; a strong acid solution is added to the heated diluted black liquor solution and stirred continuously to allow it to fully react; The solution after the reaction is allowed to settle to obtain a supernatant and a precipitate; Add deionized water to the primary precipitate, stir thoroughly, and let it stand again to obtain a secondary supernatant and a secondary precipitate; The primary precipitate and the secondary precipitate are combined and fully dried in an oven to obtain lignin; The primary supernatant and the secondary supernatant are combined, centrifuged, filtered through a microporous membrane, and the pH value of the solution is adjusted to 6-7. The obtained solution is placed in a dialysis bag for dialysis. The dialyzed carbon quantum dot solution is placed in a freeze dryer and freeze-dried to obtain carbon quantum dot powder. The concentration of the strong acid solution is 40-80%, and the temperature of the heated black liquor solution is 40-80°C.

2. The method according to claim 1, wherein: The usage ratio of the diluted black liquor solution to the strong acid solution is 10 to 20:

1.

3. The method according to claim 1, wherein: The ultrasonic oscillation time is 20 to 40 minutes.

4. The method according to claim 1, wherein: The strong acid solution is a sulfuric acid solution, a hydrochloric acid solution and a phosphoric acid solution.

5. The method according to any one of claims 1 or 4, characterized in that: The concentration of the strong acid solution is 60-80%.

6. The method according to claim 1, wherein: The static sedimentation time is 12 to 20 hours.

7. The method according to claim 1, wherein: The pore size of the microporous filter membrane is 0.22 to 0.35 μm.

8. Carbon quantum dots and lignin prepared by the method according to any one of claims 1 to 4, 6 to 7.

9. Use of the carbon quantum dots according to claim 8 as catalysts in photocatalytic degradation of pollutants.

10. The use according to claim 9, characterized in that: The application method comprises: The carbon quantum dots and TiO2 were mixed and placed in a reactor, ultrasonically shaken, and placed in a muffle furnace for reaction. After the reaction was completed, the mixture was cooled to room temperature to obtain a solid-liquid mixture. After the solid-liquid mixture is washed and centrifuged, the precipitate is dried and ground to obtain carbon quantum dots / TiO2 catalyst powder.